Economic analysis of milk production in eastern region of India - Kumari, Binita; Chandel, BS; Lal, Priyanka (Indian Journal of Dairy Science, 2020)
India maintains the top most position in milk production due to the continuous efforts of the dairy farmers of the nation who have been consistent in dairying sector despite all the vagaries. Profitability in dairy farming is important to keep the farmer into the business. Keeping this in mind the present study was taken in eastern region of India with an aim to find out the cost and return per litre of milk. The study concluded that about fifty per cent of total feed and fodder cost was incurred on concentrate and the cost incurred on feeding buffaloes was maximum followed by crossbred and local cows. About ninety per cent of the labour cost was on own family labour. Return per litre from milk was highest for crossbred and the least for local cow and it varied positively with the herd size. It was also found that the income from sale of milk can be increased if expenditure on green fodder, dry fodder, concentrate and labour used are increased Also, the farmers in the study area are over using green fodder, optimally using dry fodder and under using concentrate and labour in milk production.